Seasonal changes in the physiological activity of regeneration under a natural light gradient in a Pinus pinea regular stand - Pardos, Marta; Puértolas, Jaim; Madrigal, Guillermo; Garriga, Enrique; de Blas, Santiago; Calama, Rafael (Forest Systems, 2010)
Seasonal courses of chlorophyll a fluorescence, gas exchange parameters and water status, joined to environmental variables, were measured in four age classes of stone pine (Pinus pinea L.) natural regeneration under a natural light gradient in a stone pine regular stand throughout 2007 and 2008. One-year old seedlings were worse adapted to the extreme drought conditions recorded in summer (especially in 2008), showing lower predawn and midday Fv/Fm values, slightly lower photosynthetic rates at midday, lower PSII values, lower water potentials (pd andmin), and high mortality (90%). The oldest seedlings (class 4, 51-200 cm high), although they do not experience the lowest min in July 2008, were not able to maintain a positive carbon gain at midday, even showing the lowest photosynthetic rates. However, they rapidly recovered once the climatic conditions were softened in early autumn. During late autumn low Fv/Fm values were found especially in one-year old seedlings, indicating that maximal photochemical efficiency of PSII is sensitive to the autumn temperatures below cero recorded during both years. Thus, stone pine regeneration adapts its physiology to the seasonal course of temperature and water availability, showing a different photosynthetic performance according to age class. However, seedling physiology is not affected by the natural light gradient found in the studied stand, probably related to the low variability recorded in GSF values and the low density of the stand. We suggest that such low stand densities cannot assure one-year old seedlings’ survival, but are sufficient for older seedlings.